Implementasi Sistem Pendukung Keputusan Untuk Menentukan Guru Terbaik Menggunakan Metode Simple Additive Weighting (SAW) - Daffa Prananda Putra; Herwis Gultom (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Teacher performance evaluation constitutes a fundamental element in educational quality enhancement, yet conventional assessment mechanisms frequently encounter subjectivity and inconsistency problems. This research aims to develop a Decision Support System for identifying the best teachers at SMAN 15 Tangerang City utilizing the Simple Additive Weighting approach. The system integrates five evaluation criteria encompassing discipline, communication ability, professional attitude, learning creativity, and teaching methodology with weighting based on importance level. The development methodology adopts the Waterfall model with systematic stages from requirements analysis to system evaluation. Implementation was conducted on assessment data of 54 teachers through decision matrix normalization and preference value calculation processes. Research findings demonstrate the system's capability to generate objective rankings with the best teacher obtaining a score of 0.9729. Black Box and White Box testing validated that system functionality operates optimally with high accuracy levels. This web-based system provides transparency, accountability, and efficiency in educational management decision-making processes.